Enhancing Community Welfare: Analysis of Village Fund Management in the Socio-Economic Sector - Freitasl, Alberto da Costa; Costa, Horácio da (Institute for Law and Economics Studies, 2022)
The research investigates the impact of Village Fund management on community welfare within the socio-economic sector. The study aims to assess how effective utilization of the Village Fund influences socio-economic indicators within rural communities. Employing a mixed-method approach, data was collected through surveys, interviews, and document reviews to comprehend the relationship between fund management and community well-being. Findings revealed a positive correlation between transparent and equitable fund allocation and improvements in household income, infrastructure development, education, and healthcare services. However, challenges in transparency, disparities in fund allocation, and capacity limitations were identified, suggesting opportunities for improvement. The implications suggest that well-managed funds have the potential to uplift living standards and foster sustainable community development. Recommendations include policies for transparent allocation, capacity-building programs, and community involvement to optimize fund management and enhance community welfare. This research presents critical insights and avenues for future exploration, emphasizing the vital role of effective fund management in driving socio-economic development and promoting community welfare within rural areas.